The emergence of civilisation : the Cyclades and the Aegean in the third millennium BC - Renfrew, Colin, 1937- (Oxbow Books, 2011)
Introduction. Civilisation ; The explanation of culture change ; The multiplier effect ; The Minoan-Mycenean civilisation and its origins -- Culture sequence. The neolithic background ; Crete in the third millennium BC ; The third millennium BC in the Eastern Aegean ; The early Cycladic culture sequence ; The Grotta-Pelos culture ; The Keros-Syros culture ; The Phylakopi I culture ; Aegean interrelations and chronology in the third millennium BC -- Culture process. Patterns of settlement and population in the prehistoric Aegean ; Natural environment and the subsistence subsystem ; The development of Aegean metallurgy ; Craft specialisation and the transformation of the physical environment ; Social systems ; Symbolic and projective systems ; Trade, communication and innovation ; The multiplier effect in action -- Appendix. Gazetteer of neolithic and early Bronze Age sites in the Cycladic Islands ; Local groups with the Grotta-Pelos and Keros-Syros cultures of the Cyclades ; Data for the matrix analysis of the early Cycladic cemeteries.